Model of continuous nitration of benzene in perfect mixing reactor - Кондратов, Сергей Алексеевич; Аль Хамадани, М. Д. (Eastern-European Journal of Enterprise Technologies, 2014)
A dynamic mathematical model for the continuous nitration of benzene with a mixture of sulfuric and nitric acids in the perfect mixing reactor, taking into account chemical and physico-chemical processes, allowing to simulate processes in the industrial nitration reactor, was developed. It was found that the model has only one steady state, indicating the reactor stability. The steady state with increasing the spent acid module and reducing the residence time shifted towards reducing the degree of benzene and temperature conversion. Based on the computer simulation method of constructing the tolerance range of input variables (module and concentration of spent acid, residence time, reduced heat transfer), ensuring that the output variables (temperature and conversion degree) are in the normative specified value ranges, was developed. For a series of module values and the spent acid concentration the values of the minimum residence time were determined, the equations connecting the upper and lower boundaries of the heat transfer with the residence time in the nitration reactor were obtained. The obtained results can be used for solving problems related to the design of reactors and control systems of benzene nitration process.